1982
DOI: 10.1902/jop.1982.53.4.223
|View full text |Cite
|
Sign up to set email alerts
|

The Bacteriology of Acute Necrotizing Ulcerative Gingivitis

Abstract: Plaque samples from 22 ulcerated sites in eight patients with ANUG were cultured using quantitative anaerobic procedures and were examined microscopically. The partial characterization of the predominant cultivable flora revealed a constant flora comprised of a limited number of bacterial types and a variable flora composed of a heterogeneous array of bacterial types. This constant flora would appear to be pathognomonic of acute necrotizing ulcerative gingivitis (ANUG) and included the various Treponema and Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
191
1
6

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(202 citation statements)
references
References 26 publications
3
191
1
6
Order By: Relevance
“…P. intermedia has been commonly isolated from not only subgingival sites in adults suffering from periodontitis and various types of gingivitis, such as pregnancy gingivitis, acute necrotizing gingivitis and HIV-related gingivitis (10,13,19) but also from subgingival plaques of periodontally healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P. intermedia has been commonly isolated from not only subgingival sites in adults suffering from periodontitis and various types of gingivitis, such as pregnancy gingivitis, acute necrotizing gingivitis and HIV-related gingivitis (10,13,19) but also from subgingival plaques of periodontally healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Porphyromonas gingivalis is well known as a putative etiologic pathogen in the progression of periodontal disease, because this bacterium particularly has been associated with periodontally active diseased sites and loss of periodontal attachment (23,25,30), while black-pigmented Prevotella intermedia has been found in both periodontally diseased patients and healthy subjects (4,9,15,27,33). P. intermedia has also been reported to be associated with periapical abscess (7), pregnancy gingivitis (10), acute necrotizing ulcerative gingivitis (13) and HIV associated periodontal lesions (19). It has been suggested that P intermedia includes several biochemical, serological, and genotypical variants (1, 2, 5, 6).…”
mentioning
confidence: 99%
“…Fusobacterium species including F. nucleatum, are detected in high frequency in lesions of gingivitis and chronic periodontitis (8,9). P. intermedia and Prevotella nigrescens are frequently isolated from the periodontal lesions of patients with chronic periodontitis (8,9,10), aggressive periodontitis (11,12), puberty-associated gingivitis (13,14), and acute necrotizing ulcerative gingivitis (15). Recently, our research group reported that the average number of periodontopathic bacterial species, including P. intermedia and P. nigrescens, was significantly higher in plaque samples 5 harboring F. nucleatum and/or F. periodontium than in those without in Japanese children and mothers (16).…”
Section: Introductionmentioning
confidence: 99%
“…Increased steroid levels in the mouth could also serve as a rich nutrient source for anaerobes. 24 Thus, the patient has high risk for developing secondary infection such as noma.…”
Section: Case Managementmentioning
confidence: 99%